2000
DOI: 10.1348/135910700169008
|View full text |Cite
|
Sign up to set email alerts
|

Self‐rated menopausal status and quality of life in women aged 40‐63 years

Abstract: Objectives. To determine whether quality of life (QOL) changes during the menopause as a function of menopausal status and other medical and lifestyle variables. Design. A postal questionnaire sent to three different samples of women. Method. A total of 1188 questionnaires were received from (a) two samples recruited from two Family Health Service Association (FHSA) lists and (b) one sample recruited through an advertisement in a women's magazine. The questionnaires consisted of (a) a seven domain, 48‐item, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
5

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 24 publications
2
32
0
5
Order By: Relevance
“…Our findings are in accordance with many previous studies and confirm negative effects of menopause on quality of life. [12,13] We found that educational level of the women had positive impact on menopausal symptoms. We may interpret this as follows; if a woman is educated, she can cope better with menopausal symptoms.…”
Section: Discussionmentioning
confidence: 79%
“…Our findings are in accordance with many previous studies and confirm negative effects of menopause on quality of life. [12,13] We found that educational level of the women had positive impact on menopausal symptoms. We may interpret this as follows; if a woman is educated, she can cope better with menopausal symptoms.…”
Section: Discussionmentioning
confidence: 79%
“…Older women had a significantly better HR-QOL compared with younger women. Studies have shown that there is a decline in the prevalence of vasomotor, somatic, and psychological symptoms after menopause [3,20]. Additionally, older women may have learned to handle with menopausal symptoms over time.…”
Section: Discussionmentioning
confidence: 99%
“…The following scales are introduced according to their chronological order of construction. They are listed in Table 3 [36][37][38][39][40][41][42][43][44][45] .…”
Section: Assessment Of Health-related Quality Of Life In Aging and CLmentioning
confidence: 99%